The Influence of Implementing Cooperative Principles and Training Programs on Management Motivation and Performance from the Productivity Aspect in Savings and Loans Cooperatives in Pekanbaru City - Ayu, Widiya; Machasin, Machasin; Garnasih, Raden Lestari (Journal Of Accounting Management Business And International Research, 2025)
This research aims to evaluate the effect of implementing cooperative principles and training programs on the motivation and performance of management in savings and loan cooperatives in Pekanbaru City. The research methodology involved distributing questionnaires to 10 active savings and loan cooperatives, with a total of 30 respondents. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) statistical technique. Research findings show that the application of cooperative principles and training programs has a significant direct influence on management motivation. Apart from that, the application of cooperative principles and training programs also has a significant direct effect on the performance of cooperative management. Motivation directly influences the performance of cooperative management. Indirectly, the application of cooperative principles and training programs also influences the performance of cooperative management through motivation. This research provides important insights into the relationship between the application of cooperative principles, training programs, motivation, and the performance of cooperative administrators.